Validation of Hertzian Theory of a Cylinder Contact with a Plane Surface Using Finite Element Analysis - Chanmalai, Thanin; Chang, Byungik; Yuttapravest, Jirawat (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
In general, contact stress is generated when a force is applied between solids in contact. Contact stress addressed sufficiently severe defects that occur within the construction design, and the end material may fail to qualify. Hertz’s theory illustrates the contact stress issues at the contact regions between two elastic solids in frictionless contact. As a result, analyze the structural behavior, it requires Hertz contact stress to calculate the contact pressure between two elastic solids. In addition, the issues including complicated structural systems need to rely on numerical solutions to create an accurate solution for contact stress between two elastic solids. Therefore, the finite element method (FEM) is a numerical solution to achieve many complicated problems relevant to the contact mechanic. The primary objective of this research is to achieve the validation between Hertz contract stresses of a cylinder contact with a flat surface by using FEM.